Different response of a native dragonfly species against a neonative invader along a latitudinal gradient - Koki Nagano; Masayoshi K. Hiraiwa; Naoto Ishiwaka; Francisco Sánchez-Bayo; Daisuke Hayasaka (iScience, 2025)
Summary: The poleward expansion of various organisms is accelerating due to global warming, but many aspects of these biological invasions remain unclear. One less documented aspect is the competition among native and invader species (so-called neonatives) with similar ecological niches along a latitudinal gradient. In this study, we compared the foraging behaviors across latitudes between nymphs of the native dragonfly Orthetrum albistylum speciosum from four different Japanese regions when confronted with its neonative counterpart, Trithemis aurora. The foraging intake of O. albistylum speciosum nymphs from low-latitude regions did not change in the presence of T. aurora, whereas native populations from higher latitudes had significantly lower intakes. Our findings imply that while no clear impacts by the neonative species are found at present, threats are expected to be more severe if the invader expands its distribution to northern regions as global warming continues unabated.